Limb amputation for surgical management of grade two mast cell tumor on digit of labrador retriever - Tri Ayu Kristianty; Siti Zaenab; Osye Syanita Alamsari; Sitaria Siallagan; Sukmasari Arifah; Bagus Satrio Budiharjo (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
The Labrador retriever came to My vets animal clinic Bumi Serpong Damai with mass on digit for a month. Punch biopsy procedure was performed to differentiate the type of the cells involved. The histological report diagnosed mast cell tumor grade 2. Mast cell tumors are one of the most common skin tumors in dogs, its account for approximately 20-25% of skin tumors in dogs. Mast cell tumors can be classified as grade 1, 2 and 3 by histological assesment. Hematology, blood chemistry, chest radiography and abdomen ultrasound were taken to evaluate metastasis condition of the tumor and the results were normal. Mast cell tumors are corrected by surgical, and post-operative survival time is related to the degree of differentiation. Limb amputation was taken as an option to prevent the spread of tumor to the nearest lymph node, namely the axillary node.